A comprehensive review on sub-zero temperature cold thermal energy storage materials, technologies, and applications: State of the art and recent developments. (15th April 2021) - Yang, Lizhong; Villalobos, Uver; Akhmetov, Bakytzhan; Gil, Antoni; Khor, Jun Onn; Palacios, Anabel; Li, Yongliang; Ding, Yulong; Cabeza, Luisa F.; Tan, Wooi Leong; Romagnoli, Alessandro
Graphical abstract: Highlights: Summarizes a wide temperature range of Cold Thermal Energy Storage materials. Phase change material thermal properties deteriorate significantly with temperature. Simulation methods and experimental results analyzed with details. Future studies need to focus on heat transfer enhancement and mechanical design. Analyzes applications with technology readiness and more should be explored. Abstract: The energy industry needs to take action against climate change by improving efficiency and increasing the share of renewable sources in the energy mix. On top of that, refrigeration, air-conditioning, and heat pump equipment account for 25–30% of the global electricity consumption and will increase dramatically in the next decades. However, some waste cold energy sources have not been fully used. These challenges triggered an interest in developing the concept of cold thermal energy storage, which can be used to recover the waste cold energy, enhance the performance of refrigeration systems, and improve renewable energy integration. This paper comprehensively reviews the research activities about cold thermal energy storage technologies at sub-zero temperatures (from around −270 °C to below 0 °C). A wide range of existing and potential storage materials are tabulated with their properties. Numerical and experimental work conducted for different storage types is systematically summarized. Current and potential applications of cold thermal energy storage are analyzed with their suitable materials and compatible storage types. Selection criteria of materials and storage types are also presented. This review aims to provide a quick reference for researchers and industry experts in designing cold thermal energy systems. Moreover, by identifying the research gaps where further efforts are needed, the review also outlines the progress and potential development directions of cold thermal energy storage technologies.